Jumi extract lowered the expression of inflammatory and fibrotic components in human renal tubular epithelial cells induced by high glucose through inhibiting long noncoding RNA RMRP gene - Cheng Tao; Wang Gui-lin; Zhang Xiu-rong; Zhang Tao; Tang Qian-rong (Linchuang shenzangbing zazhi)
ObjectiveTo explore the effect and molecular mechanism of Jumi extract on the expression of inflammatory and fibrotic components in human renal tubular epithelial cells induced by high glucose （HG）.MethodsRenal tubular epithelial cells HK-2 were divided into the groups of NC （blank control），OSM （osmotic pressure control），HG （high glucose treatment），HG+ low/medium/high-dose，si-NC+HG，si-LncRNA RMRP+HG，pcDNA+HG+high-dose，pcDNA-LncRNA RMRP+HG+high-dose. Among them，NC group received 5.5 mmol/L glucose， OSM group 5.5 mmol/L glucose+24.5 mmol/L mannitol，HG group 30 mmol/L glucose，HG+low/medium/high-dose groups 30 mmol /L glucose+0.01，0.02，0.04 mg/mL Jumi extract；si-NC+HG，si-LncRNA RMRP+HG，pcDNA+HG+high-dose and pcDNA-LncRNA RMRP+HG+high-dose groups were transfected with si-NC，si-LncRNA RMRP，pcDNA，pcDNA-LncRNA RMRP before dosing 30 mmol/L glucose or 30 mmol/L glucose+0.04 mg/mL Jumi extract. Cell counting kit 8 （CCK-8） method was employed for determining cell viability，Western blot for detecting the expression of fibrosis factors α-SMA，Fn and COL1a1；enzyme-linked immunosorbent assay （ELISA） for detecting the levels of inflammatory factors TNF-α and IL-6；reverse transcription quantitative polymerase chain reaction for examining the expression of LncRNA RMRP.ResultsAt the doses of 0.01，0.02 and 0.04 mg/mL，Jumi extract gradually boosted the activity of HK-2 under high glucose and the expressions of α-SMA，Fn，COL1a1 protein，TNF-α，IL-6 and LncRNA RMRP gradually declined （P<0.05）. And si-LncRNA RMRP suppressed the expressions of α-SMA，Fn，COL1a1，TNF-α and IL-6 levels （P<0.05）. LncRNA RMRP could attenuate the inhibitory effect of Jumi extract on the expressions of inflammatory and fibrotic factors in HK-2 cells under high glucose.ConclusionsJumi extract lowers the expressions of inflammatory and fibrotic components in human renal tubular epithelial cells under high glucose through down-regulating the expression of LncRNA RMRP.